2021
DOI: 10.3390/polym13244431
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Physicochemical Properties of Modified Corn Starch–Chitosan Biodegradable Films

Abstract: Starch is a biopolymer with enormous potential for generating new biodegradable packages due to its easy availability and low cost. However, due to its weak functional properties, limitation of its interaction with some hydroxyl groups and evaluation of blends with other polymers are necessary in order to improve its performance. Glycerol-plasticized acetylated corn starch films were developed using the casting method, and the impact of incorporating chitosan (TPS:CH) in various proportions (75:25, 50:50, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
3
23
0
1
Order By: Relevance
“…In the thermal analysis curves (Figure 2), it was observed that the exhibited degradation around 300 °C. The degradation temperature (Tma film (starch/PVOH/chitosan) was consistent with data previously repor ture for each polymer [5,13]. In general, it was observed that, when in (w/w) of the different plasticizers, two thermal events resulted: the first represented the loss of humidity (see Figure 2A); the second, at appro represented the degradation of the plasticized polymer blend.…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 88%
See 3 more Smart Citations
“…In the thermal analysis curves (Figure 2), it was observed that the exhibited degradation around 300 °C. The degradation temperature (Tma film (starch/PVOH/chitosan) was consistent with data previously repor ture for each polymer [5,13]. In general, it was observed that, when in (w/w) of the different plasticizers, two thermal events resulted: the first represented the loss of humidity (see Figure 2A); the second, at appro represented the degradation of the plasticized polymer blend.…”
Section: Thermogravimetric Analysis (Tga)supporting
confidence: 88%
“…The film-forming solution was dried in an acrylic mold at 65 • C for 5 h in a convection oven (Oven Series 9000, Thermolyne). The drying process and temperature were determined according to the methodology of Calambas, Heidy Lorena, Abril Fonseca, Dayana Adames, Yaneli Aguirre-Loredo and Carolina Caicedo [6], and Jiménez-Regalado, Enrique Javier, Carolina Caicedo, Abril Fonseca-García, Claudia Cecilia Rivera-Vallejo and Rocio Yaneli Aguirre-Loredo [13]. The composite films were previously conditioned for 48 h at 25 • C and 54% RH before evaluating their physicochemical properties.…”
Section: Preparation Of Filmogenic Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, an energy absorption band was also observed around 960 cm −1 , indicating the presence of glycosidic bonds in starch due to amylopectin α-16 bonds [45]. Even though different plantain varieties were used, the FTIR is in accordance with a similar analysis carried out by F.M Pelissari et al [19] on plantain starch and flour polymeric films, as well as other starch-based films from other sources such as corn [49] and cassava [50]. In general, the main functional groups detected in TPF correspond to polysaccharides and glycosidic bonds which allow the formation of the polymeric matrix.…”
Section: Fourier-transformed Infrared Spectroscopy (Ftir)supporting
confidence: 79%